2023
DOI: 10.3390/ijms24021151
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of High-Density Lipoprotein (HDL) Quantity and Quality by Regular and Habitual Exercise in Middle-Aged Women with Improvements in Lipid and Apolipoprotein Profiles: Larger Particle Size and Higher Antioxidant Ability of HDL

Abstract: Regular exercise, especially aerobic exercise, is beneficial for increasing serum high-density lipoprotein-cholesterol (HDL-C) levels in the general population. In addition to the HDL-C quantity, exercise enhances HDL functionality, antioxidants, and cholesterol efflux. On the other hand, the optimal intensity and frequency of exercise to increase HDL quantity and enhance HDL quality in middle-aged women need to be determined. The current study was designed to compare the changes in HDL quantity and quality am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…While total HDL-P concentration decreased, mean HDL-P size increased in both training groups and when grouped together. This increase in HDL-P size has been noted in other studies and is viewed as favorable, as this change is indicative of a greater cholesterol-carrying capacity of the circulating HDL particles [16,[32][33][34] and may, in part, explain the decreased HDL-P concentrations. The same rationale can also apply to the increase in LDL-P size observed in the moderate-dose exercise group [35].…”
Section: Discussionsupporting
confidence: 69%
“…While total HDL-P concentration decreased, mean HDL-P size increased in both training groups and when grouped together. This increase in HDL-P size has been noted in other studies and is viewed as favorable, as this change is indicative of a greater cholesterol-carrying capacity of the circulating HDL particles [16,[32][33][34] and may, in part, explain the decreased HDL-P concentrations. The same rationale can also apply to the increase in LDL-P size observed in the moderate-dose exercise group [35].…”
Section: Discussionsupporting
confidence: 69%
“…Very low-density lipoproteins (VLDL, d < 1.019 g/mL), LDL (1.019 < d < 1.063), HDL 2 (1.063 < d < 1.125), and HDL 3 (1.125 < d < 1.225) were isolated from individual subject sera via sequential ultracentrifugation for 96 h [ 51 ], with the density adjusted by adding NaCl and NaBr according to standard protocols [ 52 ]. As a control serum for native VLDL and LDL, the blood from young and healthy human males (n = 10, mean age, 23 ± 2 years old) was donated voluntarily after fasting overnight.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that aerobic exercise can increase HDL capacity to promote cholesterol efflux as well as its antioxidative and anti-inflammatory activities [42,49 ▪ ]. Moreover, another study reported that daily exercise enhanced antioxidative activity of HDL in middle-aged women [50 ▪ ]. Consistent with these results, both moderate and intense exercise improved cholesterol efflux to HDL in young men [51 ▪ ].…”
Section: High-density Lipoprotein and Energy Expenditurementioning
confidence: 72%